The efficacy of enhancing carbonate weathering for carbon dioxide sequestration - Knapp, William J.; Tipper, Edward T. (Frontiers in Climate, 2022)
Enhanced weathering is a geoengineering strategy aiming to increase conti- nental weathering rates, thereby increasing the delivery of atmospheric carbon (as HCO3 – ) to the oceans. Most enhanced weathering studies focus on the capacity of silicate rocks (e.g. basalt) and minerals (e.g. olivine, Mg2SiO4 or wollastonite CaSiO3) to remove atmospheric CO2. However, carbonate minerals (e.g. calcite, CaCO3) could provide an additional, rapid way to increase HCO3 – export to the oceans. Recent work suggests 0.84 Gt C yr−1 could be removed from the atmosphere through enhanced dissolution of calcite in high-pCO2 soils, provided carbonic acid is the main dissolution agent. However, it is not clear whether atmospheric CO2 dissolved in soils can be transported by rivers, which typically have lower [ pCO2], to the oceans. This difference in calcite solubility between soils (where weathering occurs) and rivers (where HCO3 – is transported) may lead to large amounts of secondary carbonate formation during transport, releasing the CO2 consumed through dissolution. Here, we present a global modelling study comparing the estimated soil dissolution capacity (SDC) in 149 of Earth’s largest river basins, to the potential transport capacity of carbon (PTCC) in corresponding rivers. We find the SDC can only be exported to the oceans, without secondary carbonate precipitation, if rivers are in disequilibrium with respect to calcite (i.e. SIc = 1). In this instance 0.92 Gt C yr−1 may be sequestered above background weathering rates, which is ∼ 20 % of annual increases in atmospheric carbon. If rivers are at equilibrium with calcite (i.e. SIc = 0), approximately two thirds of the carbon dissolved in soil waters is lost due to calcite precipitation in rivers, and just 0.26 Gt of additional atmospheric C yr−1 can be transported to the oceans. Overall, the efficacy of enhanced carbonate weathering is a function of the capacity rivers have for transporting the products from carbonate weathering to the oceans, rather than the dissolution capacity of soils. These findings have implications for the efficiency of enhancing silicate weathering for ocean alkalinity enhancement, as secondary carbonate precipitation during transport is not always considered